CHAMPION STUDY: Childhood Assessment of Multi-organ dysfunction Post Neonatal encephalopathy - ZAREEN, ZUNERA (Trinity College Dublin. School of Medicine. Discipline of Paediatrics, 2019)
Neonatal brain injury is an important cause of neonatal death and disability such as cerebral palsy. Perinatal global hypoxic ischaemia associated with neonatal encephalopathy results in multi-organ dysfunction which may persists in later childhood. The aim of our study was to examine multi-organ dysfunction in childhood in children with neonatal encephalopathy (NE). Detailed multi organ dysfunction (MOD) was completed in infants with NE, quantified organ outcomes including serum, urine and cerebrospinal fluid (CSF) biomarkers. We followed-up this cohort at school-age measuring multiorgan outcomes at school-age compared to age matched controls and children with Cerebral palsy (CP). We also assessed the sleep pattern, quality of life (QOL) in children with NE. Persistent or sustained inflammation has been implicated in neonatal brain injury, therefore we examined the innate immune response including expression of the inflammasome, HIF-1α, CD11b and Toll-like receptor-4 expression on the surface of neutrophils and cytokine response in children with NE. We recruited children who had NE (n=55), 65 age-matched controls (n=65) and with CP and complex needs (n=26). Blood & urine samples, questionnaires (developmental, sleep and QOL) and clinical examination were performed. Increased incidence of sleep disorders and low QOL scores were seen in children with NE in comparison to children in the control group. Persistently deranged renal function including elevated urea and creatinine were found in children with NE. Persistently high white cell and neutrophil count were noted in children with NE and a correlation between low cognitive score at 2 years and elevated neonatal white cell count was noted. Increased expression of inflammasome NLRP3, HIF-1α and circadian rhythm genes were noted, increased with LPS and subsided by melatonin. Elevated cytokine response of pro and anti-inflammatory cytokines was also noted in children with NE at school age suggesting persistent altered inflammation. This study demonstrated the extent of multiorgan dysfunction (MOD) including neurological, renal, haematological involvement and sleep disorders in infants and in children who had NE. Quantifying multiorgan dysfunction in the neonatal period to ensure appropriate follow-up of all organs is merited. This would help in advanced clinical planning and long term follow up. Understanding, the immune response in these children with NE and exploring systemic inflammation holds promise for future development of immunomodulatory adjunctive therapies.
APPROVED
Keywords: Neonatal encephalopathy, childhood outcome, multi-organ dysfunction, cytokines, innate immune function, sleep and circadian genes, quality of life